BPM and cycle counting in the design of a model to increase the perfect order: a case study in a company in the commercial sector - Fernandez Lopez, Kevin Scott (2022)
This paper aims to evaluate the level of delivery compliance in an industrial tools trading company in Metropolitan Lima, based on the decrease in sales observed in the year 2020. For this reason, a quantitative and qualitative diagnosis of the company was carried out, where a low level of delivery compliance was observed, which is generating an economic impact of about 15% of the company's annual income. Furthermore, this problem is measured through the technical gap of the percentage of perfect deliveries, which is currently 64.5%, below the current market. In this sense, a model was proposed to increase the percentage of perfect orders through the implementation of Cyclic Counting, 5S, AHP and BPM in order to increase the Inventory Record Accuracy (IRA), avoid confusion in the selection of products, make an adequate selection and evaluation of suppliers and identify those activities that do not add value. In this way, the simulation of the model will be carried out and a decrease in late and incomplete deliveries will be observed, obtaining a value of 74.3% of perfect orders and a 25% increase in sales.